Bifurcation analysis of a host–parasitoid ecological model with the beddington-deangelis functional response - Agrawal, Tanuja (Global Journal of Mathematical Analysis, 2014)
In this paper, a two species host-parasitoid model system is considered. The global dynamic behavior of the model is investigated through (local) stability results for its equilibriums and large time computer simulations. Many forms of complex dynamics such as chaos, periodic windows etc. are observed. The Hopf point and attractor crises exist for different set of parameter values. Keywords: Predator-Prey; Bifurcation; Chaos; Stability.